(untitled) (American Journal of Islam and Society, 1992)
An organizational performance evaluation is one part of a larger management control process involving complex relationships between variables at the social, the organizational, and the individual levels. The philosophy, criteria, and methods used in performance evaluation vary greatly between different social and organizational cultures. In this paper, we address the issue from the perspective of a specific religion,’ Islam, and the culture which it has created, Islamic culture (IC), and compare it with a secular culture (SC). Improvement and effectiveness in secular organizations (SO) are driven by economic considerations: while Islamic organizations (IO) are required to look beyond such considerations. The supremacy of economic considerations limits an SO’S vision to thme materialistic aspects which provide the domain for deriving individual, social, and organizational goals and, at some point, everything must add up to dollars and cents. An SO also derives transitory goals from economic considerations, for its organizational process emphasizes utilitarian and objective principles which state that profit maximization (or optimization) is possible and also provides the criteria by which to measure success. In an IO, utilitarian objectives are allayed by spiritual needs, where the ideal is “reasonable profit,” and where there are sanctions against excessive profits. By definition, an organization is a purposive human system with purposes and goals which organizes and ptocesses material and human resomes for the generation of output. For an SO, output is determined by social and economic goods and services, and a system’s success is measured by its output’s quality and cost efficiency. The system’s reward is the profit earned. Most of its output and reward measures are necessarily quantitative and extrinsic in natute. An individual is, like any other part of that system, a supportive element vis-his the production of goods and services. Thus the individual is part of a process driven by economic and quantitative criteria of success, one which has no room for hisher own moral and ethical standards. In other words, religious standards play no formal role in the SO management process.